Current standards and future directions for prostate cancer radiation therapy - Pinkawa, Michael; Schoth, Felix; Böhmer, Dirk; Hatiboglu, Gencay; Sharabi, Andrew; Song, Danny; Eble, Michael J (Expert review of anticancer therapy, 2013)
Definitive radiation therapy is a well-recognized curative treatment option for localized prostate cancer. A suitable technique, dose, target volume and the option of a combination with androgen deprivation therapy need to be considered. An optimal standard external beam radiotherapy currently includes intensity-modulated and image-guided radiotherapy techniques with total doses of ≥76-78 Gy in conventional fractionation. Protons or carbon ions are alternatives available only in specific centers. Data from several randomized studies increasingly support the rationale for hypofractionated radiotherapy. A simultaneous integrated boost with dose escalation focused on a computed tomography/PET- or MRI/magnetic resonance spectroscopy-detected malignant lesion is one option to increase tumor control, with potentially no additional toxicity. The application of a spacer is a promising concept for optimal protection of the rectal wall.